Subsidies and economic and financial performance of enterprises - Štefan Bojnec; Sabina Žampa (Journal of Risk and Financial Management, 2021)
The aim of this article is to analyze the economic and financial performance of Slovenian enterprises, as a European Union (EU) member state case study. A favorable economic and financial performance is crucial for long-term sustainable enterprise growth and survival. Eight economic and financial performance indicators are used to evaluate the sustainability in the growth of enterprises: seven of them are financial indicators-assets, revenues from sales, equity, net profits, operating efficiency, return on equity, and value added per employee-while the eighth variable is the economic indicator for the number of employees. A distinction is made between enterprises that did and that did not receive subsidies from national and EU funds. Three enterprise-level data sources are combined in the empirical analysis: balance sheet data from enterprise accounts, own surveys data, and government data on public subsidies to enterprises. The mean values and standard deviations of economic and financial indicators based on balance sheet data for the years in two financial periods are estimated. The summary statistics for economic and financial indicators and correlation analysis are conducted and the results of the economic and financial indicators are compared using the parametric paired sample two-tailed t-test that allows comparison between the enterprises in the two financial periods. An increase in the economic and financial indicators is investigated by comparing the enterprises that did receive subsidies with the enterprises that did not receive subsidies in the two financial periods. The empirical results confirm that the value added per employee is the only financial indicator where a positive link is found between the financial indicator and subsidies. The results suggest that subsidies can be important for cash flow into enterprises, but entrepreneurial activities are crucial for favorable economic and financial performance and long-term sustainable growth in a competitive market environment.
Keywords: 330; economic performance; financial performance; economic indicator; financial indicators; enterprises; sustainable growth; subsidies; comparative analysis; Slovenia; European Union